2005
DOI: 10.2337/diabetes.54.3.687
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Graft Function of Adult Rat and Human Islets Encapsulated in Novel Alginate-Based Microcapsules After Transplantation in Immunocompetent Diabetic Mice

Abstract: We describe the results of the first study to show that adult rat and human islets can be protected against xenogenic rejection in immunocompetent diabetic mice by encapsulating them in a novel alginate-based microcapsule system with no additional permselective membrane. Nonencapsulated islets lost function within 4 -8 days after being transplanted into diabetic Balb/c mice, whereas transplanted encapsulated adult rat or human islets resulted in normoglycemia for >7 months. When rat islet grafts were removed 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 35 publications
4
118
0
3
Order By: Relevance
“…It has been reported that some hormone-secreting cells such as islet cells, dopaminergic cells, and parathyroid cells have been successfully microencapsulated and transplanted (Schneider et al, 2005). In this study, allotransplanted microencapsulated ovarian cells improved bone characteristics in OVX mice.…”
Section: Discussionmentioning
confidence: 76%
“…It has been reported that some hormone-secreting cells such as islet cells, dopaminergic cells, and parathyroid cells have been successfully microencapsulated and transplanted (Schneider et al, 2005). In this study, allotransplanted microencapsulated ovarian cells improved bone characteristics in OVX mice.…”
Section: Discussionmentioning
confidence: 76%
“…A long-term study of the function and graft survival with this multilayer coating scheme has not yet been performed. Nevertheless, unlike the arguably more expected durability of alginate microcapsules [15,42], the nano-layers used in this study, while being non-biodegradable, are not expected or intended to last for many months under in vivo conditions. Rather, we propose that nano-scale encapsulation is an alternative technology that may promote engraftment by allowing intraportal administration and by limiting early islet loss caused by exposure to an inflammatory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in animal models [8,9] and in human participants [10,11] have demonstrated that physical isolation of islets from the host immune system by, for example, alginate microencapsulation is effective in preventing beta cell loss and in maintaining long-term secretory function in transplanted allogeneic and xenogeneic islets without systemic immunosuppression [12][13][14][15][16]. Although conferring the immunological advantages predicted from graft/host isolation, microcapsules have some significant drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, 'living cell factory' systems can be delivered through microencapsulation for therapies such as diabetes, back pain, bone healing and osteoarthritis in a cost-effective manner. One study demonstrated that microcapsules made up of ultrahigh−viscosity alginate cross-linked with Ba 2+ and stabilized with human serum albumin (HSA) protect adult rat and human islets against xenorejection after transplantation [48] .…”
Section: Microcapsulesmentioning
confidence: 99%